Association between hospital admissions and healthcare provider communication for individuals with sickle cell disease - Cronin, Robert M (Hematology, 2020)
OBJECTIVE: To test the hypothesis that caregivers’ or adult participants’ low ratings of provider communication are associated with more hospital admissions among adults and children with sickle cell disease (SCD), respectively. Secondarily, we determined whether there was an association between the caregivers’ or participants’ health literacy and rating of providers’ communication. METHODS: Primary data were collected from participants through surveys between 2014–2016, across six sickle cell centers throughout the U.S. In this cross-sectional cohort study, 211 adults with SCD and 331 caregivers of children with SCD completed surveys evaluating provider communication using the Consumer Assessment of Healthcare Providers and Systems (CAHPS), healthcare utilization, health literacy, and other sociodemographic and behavioral variables. Analyses included descriptive statistics, bivariate analyses, and logistic regression. RESULTS: Participants with better ratings of provider communication were less likely to be hospitalized (odds ratio (OR) = 0.54, 95% confidence interval (CI) = [0.35, 0.83]). Positive ratings of provider communication were associated with fewer readmissions for children (OR = 0.23, 95% CI = [0.09, 0.57]). Participants with better ratings of provider communication were less likely to rate their health literacy as lower (regression coefficient (B) = −0.28, 95% CI = [−0.46, −0.10]). CONCLUSIONS: Low ratings of provider communication were associated with more hospitalizations and readmissions in SCD, suggesting the need for interventions targeted at improving patient-provider communication which could decrease hospitalizations for this population.